Svātmakatha - Ramāpatirāvu, Akkirāju (Bommiḍāla Śrīkṛṣṇamūrti Phauṇḍēṣan, 2018)
Felicitation volume to commemorate the 82nd birth anniversary of Akkirāju Ramāpatirāvu, born 1936, Telugu author
Keywords: Festschrift; Aufsatzsammlung; Ramāpatirāvu; Akkirāju 1936-; Authors; Telugu